The frequency exponent of artificial sandstone's complex resistivity spectrum - Jia, Jiang; Ke, S.; Rezaee, Reza; Li, J.; Wu, F. (WILEY, 2021)
The complex resistivity spectra of 16 artificial sandstone samples with different physical property at different water and solution saturations were measured and fitted with the Cole–Cole model in the frequency band of 40 Hz to 110 MHz. The frequency exponent in the model indicates the ideal degree of the sample's capacitive property. The experimental result shows that the frequency exponents of the samples are concentrated mainly between 0.82 and 0.88 and present a segmented law that decreases first and then increases with decreasing the water saturation. The minimum frequency exponent has a linear relationship with porosity and cementation index and an exponential relationship with formation factors. The frequency exponent is expected to be used in the study of the oil–water distribution in the reservoir. The frequency exponents of the samples decrease with an increase in clay content. Frequency exponents are independent of the ion type in the solution. Numerical simulation results support that the capacitive property generated by the connected pore-throat spaces is near ideal, but the capacitive property contributed by the closed pore-throat spaces is non-ideal. This could be the possible reason why the frequency exponents of the samples are less than one. The pore-throats with higher capillary pressure can be blocked and become secondary closed pore-throat space during the flooding process and result in a decrease in frequency exponent. This can explain the influence of reservoir parameters on frequency exponent and can further clarify the physical significance of the Cole–Cole frequency exponent on the rock's complex resistivity.